محاكاة النتائج التجريبية في تحليل وتصميم وصلة جائز عمود في الأبنية البيتونية الإطارية مسبقة الصنع - بسام حويجة; وليد سليمان (Tishreen University, 2016)
يتضمن بحثنا دراسة المعايير التي تضمن الأداء المتين لعقد الإطارات البيتونية, ثم اختيار نوعين من وصلات جائز-عمود تبعاً لانتشارها وتوفر علاقاتها الحسابية وإمكانية تحضيرها من المواد المحلية, ومناقشة النتائج التجريبية للدراسة المرجعية, مما يسمح لنا بإنجاز الجزء التالي من بحثنا وهو اعداد برنامج تصميمي إنشائي بلغة فيجوال بيسك بما يخدم سرعة ودقة التصميم, ويتضمن الجزء الأخير من بحثنا إجراء مجموعة من التحقيقات لإثبات صحة العمل البرمجي, ومقارنة النتائج التجريبية ونتائج الكود مع نتائج البرنامج الخاص بالبحث, لنتمكن من إجراء تحسينات هامة على هذا البرنامج ليصبح أسهل استخداماً وأكثر دقةً. Our subject contains studying criterions which ensuring a durable serving of concrete frame joints, and then choosing two connections according to its deployment and the availability of its arithmetic relations and easy to be prepared from local materials, and discuss experimental results of the resent study which allow us to achieve the next part of our research,which is a structural designing programme by visual basic language to serve the work in order to be fast and precise. the last part of the subject is comprising a number of actualizations which confirm that the process of programming is correct, and then compare the results of experimental programs and code with our programme results to achieve many important ameliorations on this programme to become more easily and better.